Identifying the single active site in MoS2-based hydrogen evolution electrocatalyst by XAFS technique. (October 2020) - Duan, Hengli; Liu, Wei; Guo, Peng; Tang, Fumin; Yan, Wensheng; Yao, Tao
Abstract: The strong metal-support interactions endow the single-atom catalysts outstanding behavior in water splitting. However, accurately characterizing the coordination and electronic structure of the active sites is still a challenge. Here, we report the synthesis of atomically dispersed Co sites anchored on the MoS2 nanosheet and discover its superior performance in the hydrogen evolution reaction (HER). The X-ray absorption spectra at both Co K -edge and L -edge reveals the coordination environment and valence state of the Co single atom, and density functional theory calculations confirm that the active sites are S atoms bonding with Co single atoms. This study suggests the promising potential of Co1 /MoS2 as a hydrogen evolution electrocatalyst. Highlights: Synthesis of Co1 /MoS2 nanosheet with Co atoms anchored on the Mo atop sites. The HER overpotential of 212 mV at 10 mA/cm 2 and Tafel slope of about 76 mV/dec. The Co 2+ valence of Co single atom. The active sites are S atoms bonding with Co single atom.